Self-reported driving difficulty in patients with bilateral cataract - Abd Rahman, Mohd Harimi; Abdul Mutalib, Haliza; Mohd Norizan, Nurul Hafizah; Md Mustafa, Md Muziman Syah (Colegio Nacional de Opticos-Optometristas de Espana, 2022)
Purpose: The presence of cataract causes reduction in visual acuity (VA) and contrast sensitivity(CS) and thus can affect individual’s daily activities. The aim of this study was to investigate self-reported driving difficulty in patients with bilateral cataract. Methods: A total of 99 participants aged 50 and above, with bilateral cataract, who possessed a valid driving license and drove regularly were chosen for this cross-sectional study that looked into their visual functions (VA and CS) and driving difficulty using the self-reported Driving Difficulty Questionnaire. Results: The mean age of the participants was 65.04§7.22 years old. Results showed that the mean composite driving difficulty score was 83.18§11.74 and most of the participants were having difficulty for driving in the rain (73.7%) and at night (85.9%). Furthermore, the study found that there was a significant correlation between driving difficulty score and CS (rs = 0.40,p= 0.03). However, there was no significant correlation between driving difficulty score and VA(rs = -0.14,p= 0.17). A linear regression was calculated to predict driving difficulty score based on binocular CS and a significant regression equation was found (F (1,28) = 8.115,p= 0.008) withR2of 0.225. Drivers with bilateral cataract will most likely experience some forms of difficulty, especially when driving under low contrast conditions.